2006
DOI: 10.1152/ajplung.00168.2006
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced mitogenic factor has proangiogenic and proinflammatory effects in the lung via VEGF and VEGF receptor-2

Abstract: . Hypoxia-induced mitogenic factor has proangiogenic and proinflammatory effects in the lung via VEGF and VEGF receptor-2. Am J Physiol Lung Cell Mol Physiol 291: L1159 -L1168, 2006. First published August 4, 2006 doi:10.1152/ajplung.00168.2006-From a mouse model of hypoxiainduced pulmonary hypertension, we previously found a highly upregulated protein in the lung that we named hypoxia-induced mitogenic factor (HIMF), also known as found in inflammatory zone 1 (FIZZ1), and resistin-like molecule ␣ (RELM␣). Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
104
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(112 citation statements)
references
References 46 publications
8
104
0
Order By: Relevance
“…Plexiform lesions can be duplicated in animal models only by VEGF receptor 2 inhibition. Interestingly, we have also shown that intravenous injection of recombinant HIMF into a mouse reduces VEGF receptor 2 expression in the lung (22). In our current study, we observed strong RELM-b immunostaining in the plexiform lesions of the scleroderma lung tissue samples, as well as of some of the idiopathic pulmonary hypertension tissue.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Plexiform lesions can be duplicated in animal models only by VEGF receptor 2 inhibition. Interestingly, we have also shown that intravenous injection of recombinant HIMF into a mouse reduces VEGF receptor 2 expression in the lung (22). In our current study, we observed strong RELM-b immunostaining in the plexiform lesions of the scleroderma lung tissue samples, as well as of some of the idiopathic pulmonary hypertension tissue.…”
Section: Discussionsupporting
confidence: 71%
“…In this study, we show that RELM-b is expressed in the pulmonary vascular smooth muscle cells of patients with scleroderma-associated pulmonary hypertension, and that the addition of rhRELM-b to primary cultured HPASMCs induces cellular proliferation as well as activation of the ERK1/2 pathway. The concentration of rhRELM-b used for the current study was similar to what was used to demonstrate HIMF-induced smooth muscle cell proliferation (15), as well as endothelial cell proliferation (22), in our animal studies. In human aortic smooth muscle cells, Calabro and colleagues (34) found that a dose of 10-100 ng/ml rhResistin was able is elicit a promitogenic response.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations